Rancang Bangun Virtual Reality Tour Video 360° Untuk Menunjang Wisata Arung Jeram Berbasis Web - Julianto, Indri Tri; Tizani, Sofyan (Institut Teknologi Garut, 2025)
The tourism sector plays a vital role in economic development, as it has the potential to increase national income, create employment opportunities, and contribute to foreign exchange earnings. Garut, a regency in Indonesia, has experienced significant changes in the number of domestic and international tourist visits over the past three years. White-water rafting on the Cimanuk River has emerged as one of the main attractions, with its class-3 river characteristics offering a challenging yet relatively safe experience, presenting great potential to attract tourists. Although promotional efforts for rafting in Garut have utilized social media platforms such as Instagram, TikTok, and Google Business, there remains considerable opportunity to enhance tourism appeal through more innovative promotional technologies. This study proposes the use of Virtual Reality Tour technology to support web-based promotion of white-water rafting tourism. This technology enables prospective visitors to virtually experience rafting through interactive and immersive 360° video. The Virtual Reality Tour application was developed using the Multimedia Development Life Cycle (MDLC) method, which includes six stages: concept, design, material collection, production, testing, and distribution. The application features text, audio, 360° panoramic images, 360° video, interactive hotspots on panoramic images, location information via Google Maps, and a live chat feature with tourism managers. Application testing yielded average scores of 88.44% for learnability, 85% for efficiency, 87.19% for memorability, 78.75% for error handling, and 87.5% for user satisfaction. Overall, the application achieved an average score of 85.38%, categorized as “very good.” These results indicate that the 360° Virtual Reality Tour application is user-friendly and can enhance the promotional experience of white-water rafting tourism on the Cimanuk River.